Security measures to ensure the intellectual property protection of internet-based publications - Tirado, Kenneth C. (School of Library and Information Studies, University of the Philippines Diliman, 2001)
Information available on the Internet are more often left unprotected in terms of intellectual property. As Internet technology becomes a common mode for people to access information, it is assumed that in the future a virtual library will emerge to cater to the needs of the public. Whatever we do, things are bound to go wrong. There isn't a single security system that is perfect. Petty theft can get away for as long as the thief is fast and careful. What we need is vigilance and determination to fulfill our duties and protect what we treasure.